2004
DOI: 10.1590/s0100-879x2004000400010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of return, gap effect and saccadic reaction time to a visual target

Abstract: Simple manual reaction time (MRT) to a visual target (S2) is shortened when a non-informative cue (S1) is flashed at the S2 location shortly before the onset of S2 (early facilitation). Afterwards, MRT to S2 appearing at the S1 location is lengthened (inhibition of return -IOR). Similar results have been obtained for saccadic reaction time (SRT). Moreover, when there is a temporal gap between offset of the fixation point (FP) and onset of a target (gap paradigm), SRT is shorter than SRT in an overlap paradigm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
(33 reference statements)
0
5
4
Order By: Relevance
“…Our results contrast with those of Abrams and Dobkin ( 1994 ) and Guimaraes-Silva et al ( 2004 ), both of whom showed an increase of saccadic IOR after the 200 ms gap. The cause of this discrepancy is unclear and worthy of further research, but we speculate that it may have arisen mainly for procedural reasons.…”
Section: Methodscontrasting
confidence: 99%
See 3 more Smart Citations
“…Our results contrast with those of Abrams and Dobkin ( 1994 ) and Guimaraes-Silva et al ( 2004 ), both of whom showed an increase of saccadic IOR after the 200 ms gap. The cause of this discrepancy is unclear and worthy of further research, but we speculate that it may have arisen mainly for procedural reasons.…”
Section: Methodscontrasting
confidence: 99%
“…The decrease of saccadic IOR and manual IOR due to the 0 ms gap contradicts the results obtained in similar studies in which the “pure” gap effect (200 ms gap) was applied (Abrams and Dobkin 1994 ; Guimaraes-Silva et al 2004 ; Hunt and Kingstone 2003 ; Souto and Kerzel 2009 ). Therefore, we conducted a second experiment in which we used the 200 ms instead of the 0 ms gap paradigm.…”
Section: Methodscontrasting
confidence: 66%
See 2 more Smart Citations
“…Whereas this confound does not challenge the different pattern of results we obtained in the blocked versus mixed conditions, one may wonder whether the removal of fixation might have reduced the measured magnitude of IOR for peripherally presented targets in our mixed condition, thus obscuring a pattern of results that would be consistent with the two-components view. This possibility can be entertained, despite Abrams and Dobkins (1994a) finding of increased IOR following fixation removal (see also Guimaraes-Silva, Gawryszewski, Portugal, & Klausner-de-Oliveira, 2004), because other researchers (Hunt & Kingstone, 2003;Souto & Kerzel, 2009) have reported the opposite finding (that fixation removal can decrease IOR). Because the possible contribution of fixation removal in Experiment 1 is, on the basis of the literature, ambiguous, Experiment 2 was conducted to determine whether IOR would continue to be equivalent for peripherally and centrally presented targets in a mixed design when the fixation removal confound was eliminated (a fixation stimulus remains onscreen throughout the trial on both peripheral and central trials).…”
Section: Discussionmentioning
confidence: 94%